Museums and social activism engaged protest - Message, Kylie (Museum meanings, 2014)
"Museums and Social Activism is the first study to bring together historical accounts of the African American and later American Indian civil rights-related social and reform movements that took place on the Smithsonian Mall through the 1960s and 1970s in Washington DC with the significant but unknown story about museological transformation and curatorial activism that occurred in the Division of Political and Reform History at the National Museum of American History at this time. Based on interdisciplinary field-based research that has brought together cross-cultural and international perspectives from the fields of Museum Studies, Public History, Political Science and Social Movement Studies with empirical investigation, the book explores and analyses museums'--specifically, curators'--relationships with political stakeholders past and present. By understanding the transformations of an earlier period, Museums and Social Activism offers provocative perspectives on the cultural and political significance of contemporary museums. It highlights the relevance of past practice and events for museums today and improved ways of understanding the challenges and opportunities that result from the ongoing process of renewal that museums continue to exemplify."